2016
DOI: 10.1016/j.biortech.2016.01.103
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of Scenedesmus obliquus in liquid hydrolysate from flash hydrolysis for nutrient recycling

Abstract: The production of biofuels from microalgae is associated with high demands of nutrients (nitrogen and phosphorus) required for growth. Recycling nutrients from the residual biomass is essential to obtain a sustainable production. In this work, the aqueous phase obtained from flash hydrolysis of Scenedesmus sp. was used as cultivation medium for a microalga of the same genus, to assess the feasibility of this technique for nutrient recycling purposes. Batch and continuous cultivations were carried out, to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Our previous studies [19][20][21][22] reported protein extraction from microalgae via bench-scale flash hydrolysis (FH). The FH process has shown to be one of the most efficient approaches in selectively hydrolyzing proteins to peptides and amino acids in short residence times (10 s) using a continuous flow reactor operated at 2808C.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies [19][20][21][22] reported protein extraction from microalgae via bench-scale flash hydrolysis (FH). The FH process has shown to be one of the most efficient approaches in selectively hydrolyzing proteins to peptides and amino acids in short residence times (10 s) using a continuous flow reactor operated at 2808C.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous work, it was shown that Scenedesmus sp. was able to uptake the organic nitrogen forms contained in the medium and use that for growth . However, the capability of up‐taking simple organic nitrogen is species‐dependent, and has therefore to be assessed for the species considered .…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, flash hydrolysis (FH) has been proven to be a sustainable continuous process that can utilize the wet algal biomass (slurry) at 280°C temperature and very short residence time (9 s) to fractionate macronutrients such as nitrogen and phosphorous while preserving lipids in the solid residue (biofuels intermediates) . The successful realization of short residence times for fractionating algae components (proteins and lipids) would greatly reduce the reactor volume, significantly reduce CAPEX and OPEX, and provides product stream of small peptides and amino acids as a co‐product along with the lipid‐rich solids as biofuels precursors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations